DISTINGUISHING LOYALTY AND CUSTOMER SATISFACTION OF XIAOMI SMARTPHONE IN YOUNG WORKERS SIDOARJO - Moh Wahib; Hendra Dwi Prasetyo (Media Mahardhika, 2020)
Photographing activities become the most activities carried out by customers and uploaded to social media in Indonesia and even in the world. Taking pictures of yourself or objects is a part of community life in Sidoarjo. In addition to following the right market trends, for companies to maintain customer satisfaction and loyalty. Satisfaction of the product will affect the customer in taking the next attitude. The customer is satisfied with a repeat purchase and will say good things about the product. Research conducted in the form of case studies on XIAOMI Smartphone users in Sidoarjo. This research is an in-depth study of one case or one unit and the conclusions in this study only apply to the case in question, so it cannot be used in other cases. The results in this study that there are differences in the level of customer satisfaction and loyalty of XIAOMI smartphone users by sex. Independent Samples t-test showed significant differences in customer satisfaction in males and females and showed significant differences in customer loyalty in males and females. The mean value indicates that female customer satisfaction and loyalty is higher than male customers.